Socioeconomic inequality and adjustments in children's perceptions of their agency as they age in South Korea. (30th March 2020) - Kim, Chae‐Young; Gewirtz, Sharon
Abstract: This paper explores how children's perceptions of their agency, as something that is closely associated with its exercise, appear in relation to social structural factors, especially their socioeconomic positions, as they age. Using data from 862 10–18 years old in South Korea, we examine how children's expressed optimism about their ability to achieve their occupational choices can conceal the impact of structural factors on their 'choices' and dispositions for (non‐)action over time. Based on the findings, we argue for a more careful interpretation of children's sense of agency that recognises its propensity to continuously adjust in contexts of structural inequality.